Perencanaan Sistem Instalasi Plambing Air Bersih dan Air Limbah di Apartemen Menara Cibinong Tower C - Rhezaldy Pradestama Putra; Kancitra Pharmawati; Anindito Nurprabowo (Jurnal Serambi Engineering, 2022)
The high population growth demands the need for housing, so apartments are considered as a solution in meeting the need for housing. Basically, every business or development activity has an impact on the environment, both positive and negative. Plumbing systems for clean water, waste water and ventilation in buildings can reduce the possibility of environmental pollution and health problems. This study aims to meet the needs of clean water and maintain the sanitation health of building occupants. The reference method is SNI 7065-2005 for calculating the need for clean water and SNI 8153-2015 for determining the dimensions of clean water pipes. The calculation results the population in the Cibinong Tower C apartment building is 957 people with a total need for clean water of 87.95 m3/ day. In meeting the daily needs of clean water in the planning building, a ground water tank with a capacity of 120 m3 is used and a roof tank is used to fulfill water needs at certain hours with a capacity of 49 m3. To distribute water from GWT to RT using a pump with a power capacity of 33.44 Kwatt. The diameter of the clean water pipe uses dimensions from 20 mm to 125 mm. For blackwater wastewater using pipes with dimensions of 60 mm–140 mm and for greywater wastewater using pipes with dimensions of 32 mm–114 mm, while for ventpipes using pipe dimensions of 42 mm–114 mm